A novel composite membrane for simultaneous separation and catalytic degradation of oil/water emulsion with high performance. (February 2022) - Rao, Linhua; You, Xiujia; Chen, Binghong; Shen, Liguo; Xu, Yanchao; Zhang, Meijia; Hong, Huachang; Li, Renjie; Lin, Hongjun
Abstract: It is of great significance to develop novel membranes with dual-function of simultaneously separating oil/water emulsion and degrading the contained water-miscible toxic organic components. To meet this requirement, a dual-functional Ni nanoparticles (NPs)@Ag/C-carbon nanotubes (CNTs) composite membrane was fabricated via electroless nickel plating strategy in this study. The as-prepared composite membrane possessed superhydrophilicity with water contact angle of 0° and splendid underwater oleophobic property with oil contact angle of 142°. When the membrane was applied for separation of surfactant stabilized oil-in-water emulsion, high permeate flux (about 97 L m −2 ·h −1 under gravity), oil rejection (about 98.8%) and antifouling property were achieved. Benefitting from the NiNPs@Ag/C-CNTs layer on membrane surface, the composite membrane exhibited high catalytic degradation activity for water-miscible toxic organic pollutant (4-nitrophenol) with addition of NaBH4 in a flow-through mode. Meanwhile, the NiNPs@Ag/C-CNTs composite membrane possessed excellent durability, which was verified by the good structural integrity even under ultrasonic treatment. The cost-efficiency, high separation and degradation performance of the prepared membrane suggested its great potential for treatment of oily wastewater. Graphical abstract: Image 1 Highlights: a NiNPs@Ag/C-CNTs membrane was made via vacuum filtration plus electroless plating. The composite membrane possessed superhydrophilicity and splendid underwater oleophobicity. The membrane enables simultaneous separation and catalytic degradation of oil-in-water emulsion. The composite membrane has high permeability, oil rejection and excellent antifouling properties. The composite membrane exhibited excellent durability under ultrasound.